2021
DOI: 10.3389/fpsyg.2021.614184
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Interventions and Foreign Language Anxiety: A Systematic Review With Narrative Approach

Abstract: Experimental studies have developed, conducted, and evaluated classroom interventions for foreign language anxiety (FLA) reduction. However, various characteristics of those classroom interventions make it difficult to synthesize the findings and apply them to practice. We conducted what is, to the best of our knowledge, the first systematic review on educational interventions for FLA. Six criteria were established for inclusion of studies. Using English keywords, we identified 854 potentially eligible studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 81 publications
1
21
0
Order By: Relevance
“…With the advent of the pandemic, most instruction previously offered in traditional formats migrated to online and "hybrid" platforms such as Skype and Zoom. Toyama & Yamazaki (2021) found that students are relatively comfortable with English autonomous learning in a multimedia network environment, especially for online learning environments. Of course, their subjects were all engineering students with a high degree of technical expertise and a strong desire to learn English.…”
Section: Technology Concernsmentioning
confidence: 96%
“…With the advent of the pandemic, most instruction previously offered in traditional formats migrated to online and "hybrid" platforms such as Skype and Zoom. Toyama & Yamazaki (2021) found that students are relatively comfortable with English autonomous learning in a multimedia network environment, especially for online learning environments. Of course, their subjects were all engineering students with a high degree of technical expertise and a strong desire to learn English.…”
Section: Technology Concernsmentioning
confidence: 96%
“…Such speaking activities can provoke students’ anxiety (Horwitz et al, 1986; Young, 1990) and language classrooms requiring such activities “are more anxiety-provoking than traditional classrooms” (Horwitz, 2001, p. 116). Even though FL learners who are anxious about speaking in class have been identified in various countries (Toyama & Yamazaki, 2021a), the degree of FLA in classroom contexts may vary based on cultural differences in individualism versus collectivism. Among these culturally different groups, there will be a clear distinction in terms of what teachers expect students to do based on norms of their societal and educational experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second/foreign language anxiety (FLA) is common in classrooms (Dewaele & MacIntyre, 2014; MacIntyre, 2017). A recent systematic review of intervention studies to reduce students’ FLA included 17 countries/regions as research locations for 40 studies (Toyama & Yamazaki, 2021a). The review consisted of only experimental studies meeting specific criteria, inferring that FLA has been studied across many countries and regions.…”
Section: Introductionmentioning
confidence: 99%
“…According to Toyama and Yamazaki (2021), in comparison to L1 acquisition, nonnative language learning (be it L2, L3 or beyond) is remarkably associated with emotions. This is especially so for adults, who are often subject to more complex psychological and emotional variables (Hershner, 2016).…”
Section: Adult Learnersmentioning
confidence: 99%